The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1080/19942060.2018.1552202
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of compressible and incompressible numerical methods in simulation of a cavitating jet through a poppet valve

Abstract: The regime of compressible flow generally refers to the super/subsonic case. However, several remarkable cases with low Mach number could not be appropriately described with the incompressible method. It is a similar case for a cavitating jet inside a poppet valve. In order to comprehensively address the discrepancy between incompressible and compressible methods, both non-cavitating and cavitating cases are performed in experiment and calculation based on OpenFOAM. Experiment reveals a transition in flow patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Due to throttling loss, the pressure drops sharply at the recovery valve, when the pressure drops to the saturated vapor pressure of the oil, gas will be released from the oil around the recovery valve. Because the oil is mixed with large bubbles, resulting in the oil presents a non-contact state, this phenomenon is known as the hydraulic shock absorber cavitation phenomenon (Yuan, Song, & Liu, 2019).…”
Section: Mechanism Of Cavitation Phenomenonmentioning
confidence: 99%
“…Due to throttling loss, the pressure drops sharply at the recovery valve, when the pressure drops to the saturated vapor pressure of the oil, gas will be released from the oil around the recovery valve. Because the oil is mixed with large bubbles, resulting in the oil presents a non-contact state, this phenomenon is known as the hydraulic shock absorber cavitation phenomenon (Yuan, Song, & Liu, 2019).…”
Section: Mechanism Of Cavitation Phenomenonmentioning
confidence: 99%
“…Furthermore, the computational fluid dynamics (CFD) technology has been increasingly used in the research of the multiphase pumps, valves or other multiphase flows (Hao & Tan, 2018;Yuan et al, 2019). And the CFD reliability has been confirmed by the comparisons with experimental tests (Ramezanizadeh et al, 2019;Yu et al, 2015Yu et al, , 2019.…”
Section: Introductionmentioning
confidence: 98%
“…Previous experimental evidence (Kumagai et al, 2016) indicated that an intimate interrelationship exists between the periodic behavior of the cavitating bubbles and the induced pressure fluctuation inside a poppet valve, but the underlying mechanisms associated with the microscopic flow dynamics have not been thoroughly clarified. Notably, an earlier study on numerical methods for a transitional cavitating jet (Yuan et al, 2019b) motivated a two-dimensional transient simulation of the cavitating jet inside an oil poppet valve, which revealed the complicated correlation between cavitation evolution and flow performance. However, owing to the much smaller viscosity of water fluid, the unsteady behavior of a water cavitating jet may display a substantial difference from that of an oil cavitating jet, and simulation of the water cavitating jet requires both an elaborate numerical treatment and significantly more computational resources to resolve the small-scale vortex cavitation structure featured with both three-dimensionality and highly transient characteristics.…”
Section: Introductionmentioning
confidence: 99%